2014
DOI: 10.4049/jimmunol.1300591
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of TLR2 or TLR4 with HLA-DR Potentiates the Superantigenic Activities ofMycoplasma arthritidis–Derived Mitogen

Abstract: Mycoplasma arthritidis–derived mitogen (MAM) is a member of the superantigen family that structurally differs from other members while still capable of initiating cognate APC/T cell interaction. In addition to the critical role of MHC class II molecules, it has been suggested that TLR2 and TLR4 may cooperate with MHC class II during MAM-induced responses. In this study, we investigated the direct involvement of TLR2 and TLR4 in MAM binding and presentation to T cells. Our results showed that MAM fails to bind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
9
0
2
Order By: Relevance
“…In addition, Mu et al (2005Mu et al ( , 2011 used TLR blocking antibodies and TLR2 or TLR4 deficient mice to show that MAM interacts directly with certain TLRs, possibly by cross-linking them with MHC class II molecules. The interaction is potentiated by co-expression of the MHC class II cell-surface receptor HLA-DR (Shio et al, 2014). The TLR2 + /TLR4 + mouse TH cytokine response to MAM is anti-inflammatory, dominated by IL-4, IL-6 and IL-10, but in TLR4 -mice a proinflammatory IFN, TNF and IL-12 response dominates.…”
Section: Specific Effector Proteins and Lipidsmentioning
confidence: 99%
“…In addition, Mu et al (2005Mu et al ( , 2011 used TLR blocking antibodies and TLR2 or TLR4 deficient mice to show that MAM interacts directly with certain TLRs, possibly by cross-linking them with MHC class II molecules. The interaction is potentiated by co-expression of the MHC class II cell-surface receptor HLA-DR (Shio et al, 2014). The TLR2 + /TLR4 + mouse TH cytokine response to MAM is anti-inflammatory, dominated by IL-4, IL-6 and IL-10, but in TLR4 -mice a proinflammatory IFN, TNF and IL-12 response dominates.…”
Section: Specific Effector Proteins and Lipidsmentioning
confidence: 99%
“…In mice treated with anti-B7-1 antibody, both MAM and TLR4 were required for a systemic and local joint stimulation of the Th17/IL-17 cascade illustrating how microbial agonists can promote chronic inflammatory and autoimmune disease by redirecting signaling pathways [218]. Interestingly, Shio et al [219] have recently shown that MAM is unable to bind directly to TLR2-and TLR4-transfected cells. However, coexpression of TLR2 or TLR4 with HLA-DR significantly increased MAM binding and subsequent T cell stimulation compared to cells expressing HLA-DR alone.…”
Section: The Role Of Tlr2 and Tlr4 In Mam Activitymentioning
confidence: 99%
“…Toll‐like receptor‐4 ( TLR4 ) is a family member of pattern recognition receptors that play important roles in mediating the inflammatory response [7–9]. TLR4 is mapped to 9q32‐q33 region and contains three exons, which participates in immuno‐regulation by suppressing T lymphocyte proliferation and regulating macrophage function [10–12]. TLR4 has been shown to play an important in the development of cardiovascular diseases [13].…”
Section: Introductionmentioning
confidence: 99%